Estrutura populacional e história demográfica das populações de baleias jubarte (Megaptera novaeangliae) da América do Sul - Souza, Ana Lúcia Cypriano de (2013)
Commercial whaling mainly during the 20th century reduced most populations of humpback whale (Megaptera novaeangliae). Seven breeding stocks (A-G) are recognized by the International Whaling Commission (IWC) in the Southern Hemisphere. Humpback whales from Breeding stock A (BSA) are distributed along the Brazilian coast (mainly between 5° and 23° S), in the Southwestern Atlantic, while the humpbacks from breeding stock G (BSG) occur from Peru (6° S) to Costa Rica (12° N) coast, in the eastern Pacific Ocean. Despite previous studies have provided important information about both South America breeding grounds, the degree of connectivity and differentiation between these populations needs to be better investigated. Therefore, the manuscript 2 of this thesis represents the first analysis of the genetic differentiation and level of gene flow between these populations, using mitochondrial DNA sequences and 16 microsatellite loci. Our results showed a significant differentiation between Breeding Stocks A and G, at both molecular markers (mtDNA and microsatellites), in specially through the Bayesian clustering analysis that identified two populations even without sampling location information. However, the assignment tests have indicated an exchange of individuals between these populations, but with a gene flow low enough to allowing the demographic independence of these two stocks. Our data segregated by gender showed a significant differentiation between females from Brazil and Colombia, and between males from Brazil and Antarctic Peninsula, suggesting higher fidelity of females to the breeding areas and of males to the feeding areas. Nevertheless, recent studies have shown females undertaking long movements between breeding grounds. Thus, a sampling effort mainly on arrival and departure of the whales migrating for these areas is needed for a better understanding of the migratory pattern of the humpbacks of these populations. Although the Brazilian humpback whale population has shown signs of recovery after suffering a reduction estimated to 2% of its historical size in the late 1950s, no genetic study has provided estimates of effective and census size, contemporary and historical, for this population. For a better understanding of the whaling impact on this population, its demographic history was investigated using different molecular markers and methods (manuscripts 1 and 3). In the first manuscript ten microsatellite loci were used to estimate for the first time its contemporary population size. In the manuscript 3 was used for the first time the high throughput sequencing technology to sequence multiple nuclear loci at 24 Brazilian humpback samples. Despite the approximate Bayesian computation analysis has supported a scenario of constant Ne over size changes scenarios during the whaling period; our estimates of contemporary size at different time frames have detected a fluctuation of the population size during this period (~ 2 to 4 generations ago). Moreover, multiple sequence loci data have indicated a most recent bottleneck caused by anthropogenic population depletion over past 200 years. Our estimate of historical abundance (~ 148,000 individuals) indicates that BSA humpback population was much larger than that estimated (24,700 individuals) by whaling catch records. Finally, an extended Bayesian skyline plot of the nuclear loci indicated that the population was declining ever since a size peak around 30,000 years ago, which may be associated with the climate changes caused by glacial/interglacial cycles. These results suggest that Southwestern Atlantic humpback population was higher before the onset of the whaling period, which may explain the discrepancy found between previous genetic and catch record population size estimates at this period.